Effect of fly ash addition on mechanical properties and fracture mechanisms of concrete - Khoo Dei Xiong (School of Environmental Engineering, University Malaysia Perlis, 2012)
The effects of fly ash to act as partial replacement of sand onto mechanical properties and fracture mechanisms of concrete are study. This product is believe able to replace the conventional ordinary concrete and even fly ash-cement concrete after undergo several test such as x-ray fluorescent test, density analysis, setting time analysis and compression test. Where concrete which used 25% fly ash as partial sand replacement in this study had shown lesser possibility of chemical reaction to occur during concrete hydration process, besides having faster setting time, lower density and most importantly, it had the highest compressive strength among all other samples. While from environmental perspective, this study aims to reduce the waste materials of fly ash and to sustain usage of concretes raw material. The effects of fly ash addition as supplementary cementitious material on mechanical properties and fracture mechanisms of concrete are evaluated.